Pathogenicity of Mycoplasma bovis isolates from some States in Nigeria inoculateci intramammarily into lactating New Zealand white rabbits (2019)
The focus of this study was to test thè pathogenicity of Mycoplasma bovis isolated from cases of clinical mastitis in cattle in some States of Nigeria. Pathogenicity study of Mycoplasma bovis was carried out using five New Zealand White lactating rabbits, obtained from a locai breeder in Ibadan, Nigeria. The left mammary glands of each rabbit were inoculated intracisternally with Imi of 2.4 x IO5 cfu/ml of Mycoplasma bovis obtained from cases of clinical mastitis in Nigeria. The right mammary glands served as control and received 1 mi of sterile Tryptose Soy broth each. The clinical signs, post-mortem and histological findings were recorded. Clinically, thè rabbits were weak and anorexic with mortalities. Grossly, lesions were observed in thè spleens, lungs and thè ovaries, while thè mammary glands were atrophied. This clearly showed thè septicaemic nature of thè Mycoplasma bovis isolated from thè clinical mastitis cases hence proper hygienic practices should be implemented during milking for public health reasons.